Birth Tourism Among Chinese Women. Issue 2 (March 2019) - Jaramillo, Juanita; Goyal, Deepika; Lung, Carmen
Abstract: Purpose: To explore the reasons why some Chinese women travel to the United States on a tourist visa specifically to give birth, also known as birth tourism. Study Design: Qualitative, exploratory design. Methods: Using convenience and snowball sampling, Chinese women were recruited from the waiting rooms of obstetricians known to care for birth tourists. Participants completed demographic data and provided answers to questions about their reasons for traveling to give birth and their birth experience while in the United States. Qualitative content analysis methods were used to extract themes from participant narratives. Results: Twelve married, college-educated women, aged between 26 and 39 years, self-identifying as birth tourists from China participated in this study. Content analysis revealed two themes: (1) positive perceptions of childbirth in the United States; and (2) securing a future for their child. Clinical Implications: Study findings suggest Chinese birth tourists come to the United States for a better childbirth experience, and to secure future opportunities for their children. Nurses should be aware of the current political climate on immigration and birth tourism in order to promote a safe and judgment-free environment when providing care to this unique population of women. Abstract : Approximately one-third of women who come to the United States to give birth on a tourist visa are from China. In this study, birth tourists from China describe their reasons for choosing this path and their experiences. Reasons include establishing American citizenship for their baby, and thus securing them a better future, and having a painless childbirth. These data can be useful for nurses caring for women who are birth tourists.